The Use of VLab Plantae to Promote Junior High School Science Students’ Conceptual Understandings of Plant Growth and Development - Rahma, Syaffa Diah Aulia; Yusmar, Firdha; Bachtiar, Rayendra Wahyu (LPPM Universitas Bina Bangsa, 2025)
We used a qualitative approach with an explanatory case study method to examine students' conceptual understandings of plant growth and development before and after using the VLab Plantae application. Task-based interviews were applied to 12 ninth-grade students from class IX. Before and After interview, their conceptual understandings of four domains were examined, i.e., imbibition, germination, growth factors, and the growth process. The students were tasked to work with VLab Plantae based on interview protocols. The findings show that VLab Plantae improves students’ conceptual understandings, with the most significant gains in imbibition. Students grasped germination and growth processes through visual experiments with red beans and corn seeds. While all concepts in the four domain were identified during the use of VLab Plantae, our study suggests that teachers remain crucial in guiding students to use the VLab Plantae to comprehend the related concepts.